Pengenalan Metode Webbing kepada Guru untuk Pengembangan Karakter Awareness, Speaking, dan Komunikasi Peserta Didik - Martawijaya, M.A.; Haris, Abdul; Mahir, Mahir; Taqwin, Muhammad; Saleh, Muh. (LP2M Universitas Muhammadiyah Enrekang, 2024)
The webbing method has become a popular approach in modern teaching for developing various student skills. This article discusses the introduction of the webbing method to teachers as a tool to enhance student awareness, speaking abilities, and communication. The webbing method utilizes concept maps or visual diagrams to connect ideas, allowing students to organize their thoughts more structurally. Its benefits include developing character awareness through self-exploration, improving speaking skills by planning presentations, and fostering communication skills through group collaboration. Implementation steps of the webbing method include topic selection, group division, clear instructions, use of aids, and presentation with discussion of results. By integrating the webbing method into teaching, teachers can prepare students to become more self-aware and communicative individuals in the future